Strategic Leadership and SMEs Performance in Indonesia: The Mediating Role of Dynamic Human Resource Capability - Engga Jalaludin; Eeng Ahman; Amir Machmud; Yana Setiawan (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
Drawing on the Dynamic Capability View and Strategic Human Resource Management literature, this study examines the mediating role of dynamic human resource capability (DHRC) in the relationship between strategic leadership and the performance of small and medium-sized enterprises (SMEs) in Indonesia. Data were collected through a cross-sectional survey of 287 SME owners and managers across six provinces in Java and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that strategic leadership is positively associated with DHRC (β = 0.794, p < 0.001) and SME performance (β = 0.192, p = 0.021). DHRC is also positively associated with SME performance (β = 0.622, p < 0.001). Furthermore, DHRC partially mediates the relationship between strategic leadership and SME performance, as demonstrated by a significant indirect effect (β = 0.494, p < 0.001). These findings suggest that the contribution of strategic leadership to SME performance is largely transmitted through adaptive human resource routines involving learning, integration, and reconfiguration. The study extends the Dynamic Capability View by identifying DHRC as a human resource micro-foundation that helps translate strategic leadership into organizational performance in resource-constrained SME contexts.